The Requirement Scheme for Tarannum Smart Learning Application - Mohd Zaini Bin Zakaria; Hapini Awang; Nur Suhaili Mansor; Mohd Faiz Mohd Yaakob; Ramlan Mustapha; Abdulrazak F. Shahatha Al-Mashhadani (Journal of Contemporary Social Science and Education Studies, 2024)
Vol. 2 No. 2